On geometry of warped product semi invariant submanifolds of nearly (ε, δ)-trans sasakian manifold with a certain connection - Shamsur Rahman; Sabi Ahmad; Niranjan Kumar Mishra (Journal of Hyperstructures)
In this paper, we study the geometry of warped product semi invariant submanifold of a nearly (ε, δ)-trans-Sasakianmanifold M with a quarter symmetric non metric connection. We see that warped product of the typeE⊥×yET is a usual Riemannian product of E⊥ and ET , where E⊥ and ET are anti-invariant and invariant submanifolds of a nearly (ε, δ)-trans-Sasakian manifold with a quarter symmetric non metric connection M, respectively. We also obtain a characterization for such type of warped product.